Free cash flow, ownership structure, and capital structure: Impact on agency cost - Aditya, Yoga Khomaini; Laela Ermaya, Husnah Nur; Dyah Pita Sari, Ratna Hindria (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2020)
The difference in interests between investors and company managers creates a conflict of interest, so in this case, a solution is needed to reduce this problem, namely by issuing an agency cost. This study was conducted to determine the effect of free cash flow, managerial ownership, outsider block ownership, and capital structure on agency costs in Indonesia. The population in this study were all non-financial sector companies that have been listed on the Indonesia Stock Exchange for the 2014-2018 period using multiple regression analysis techniques. The results of this study explain that free cash flow, managerial ownership, and capital structure have a significant positive effect on agency cost. Meanwhile, ownership of an outsider block does not affect agency cost. This study contributes to the science of corporate governance, especially the mechanism for reducing agency costs, and contributes to the non-financial companies themselves to reduce agency costs with manager or manager ownership programs and the right decisions in the use of corporate debt.